The inflammation process of gout arthritis and its treatment - Nita Parisa; Muhammad Totong Kamaluddin; Masagus Irsan Saleh; Ernawati Sinaga (Wolters Kluwer Medknow Publications, 2023)
Gout arthritis is an inflammatory condition that occurs suddenly in joints affected by high uric acid levels (hyperuricemia). The uric acid levels in this disease fluctuate throughout its various phases, resulting in frequent or recurrent attacks. This study aims to review some aspects of gout arthritis, such as its pathophysiology, treatment goals, and adverse drug reactions. This study employs review literature using articles published between 2017 and 2022 as the research methodology. Furthermore, articles under 2017 are used as references if they are relevant to the study's subject matter. The findings showed the importance of the pathogenesis of inflammation in the treatment of gout arthritis. It is also recommended to use anti-inflammatories such as colchicine and uric acid-lowering medications starting at a specific time to prevent unintended risks. Hence, pharmacotherapy management's adverse effects include nausea, vomiting, myalgia, neuropathy, and stomach pain.